Studi Dampak Penambahan Abu Cangkang Kemiri terhadap Kekuatan Aspal Penganti Filler pada Kekerasan AC- WC - Taufik, Taufik; TM Rezaka Alfitra; Jiwa Malem Marsya; Jetno Harja; Michel Kasaf (Yayasan Literasi Sains Indonesia, 2025)
Southeast Aceh Regency is one of the hazelnut-producing areas that produces large amounts of shell waste. This study aims to utilize hazelnut shell ash as a replacement filler in the Asphalt Concrete – Wearing Course (AC-WC) mixture with variations in 2%, 3%, and 4% levels, as well as an optimal asphalt content of 6.4%. The test was carried out using the Marshall Test method referring to the 2018 General Specification of Bina Marga to assess the parameters of stability, flow, Void in Mix (VIM), Void in Mineral Aggregate (VMA), Void Filled with Bitumen (VFB), and Marshall Quotient (MQ). The results of the study showed that all parameters met the specification limits of Bina Marga 2018. The stability value increased with the addition of filler content, from 1464.00 kg (2%) to 1749.67 kg (4%). The flow value is in the range of 2–4 mm, VIM is in the range of 3–5%, VMA is above 14%, and VFB is above 65%. Although the MQ value decreases with increasing filler levels, all values remain above the minimum standard. In conclusion, hazelnut shell ash is effectively used as an alternative filler that is able to improve the technical performance of the AC-WC mixture while providing environmental benefits through the use of organic waste